Aminosidine (paromomycin) in the treatment of leishmaniasis imported into the United Kingdom. - Scott, J; Davidson, R; Moody, A; Grant, H; Felmingham, D; Scott, G; Olliaro, P; Bryceson, A (1992)
We report 11 patients with leishmaniasis from different endemic areas, treated in the UK with intravenous aminosidine alone or in combination with other drugs. Clinical and parasitological cures were achieved in all 7 patients from the Mediterranean zone who had visceral disease, with one relapse. Two of 4 patients with cutaneous or mucosal disease were cured; the other 2, from Iraq and Iran, did not respond. Toxic effects were high-tone deafness in 2 patients, one of whom had pre-existing renal impairment, and transient, mild elevation of serum creatinine in 3. Aminosidine is an effective, tolerable and relatively non-toxic alternative to existing antileishmanial drugs for the treatment of visceral leishmaniasis. Further studies will be needed to assess its place in cutaneous and mucosal disease.